Comparative Study of Protection of Migrant Workers between Desbumi's Wonosobo District and Sbmi's Kendal District (Universitas Terbuka, 2023)
The problems of female migrant workers cannot be separated from the discourse on gender inequality. Position and social construction regarding women affect the protection and treatment of migrant workers when working abroad. Likewise, when migrant workers return to their place of origin, they encounter problems from their own families. Moving on from this problem, the researcher wants to raise concerns about how the protection of migrant workers is carried out by DESBUMI in Wonosobo Regency and how the protection of migrant workers is carried out by SBMI in Kendal Regency. The purpose of this research is to find out the comparison of legal protection used to protect migrant workers in both Wonosobo and Kendal districts. The research methodology itself uses a qualitative approach to empirical juridical research. Where there are primary and secondary data. For data collection techniques using interviews, observation, and documentation. Meanwhile, for data analysis using comparative techniques (comparisons) related to the protection of migrants from two districts in Central Java between DESBUMI and SBMI. The results of the research show that protection through DESBUMI There are several services available at DESBUMI including information services, document services, economic empowerment, paralegals, Village Regulations, safe migration and data collection on migrant workers and their families. Meanwhile, SBMI focuses more on policy advocacy related to problems faced by PMI starting from pre-departure, placement and return of PMI to Indonesia.